2017
DOI: 10.1007/s12034-017-1390-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of $$\upbeta $$ β -phase development in spin-coated PVDF thick films

Abstract: A study was conducted to ascertain the effect of variation in spin speed and baking temperature on β-phase content in the spin-coated poly(vinylidene fluoride) (PVDF) thick films (∼4−25 μm). Development of β-phase is dependent on film stretching and crystallization temperature. Therefore, to study the development of β-phase in films, stretching is achieved by spinning and crystallization temperature is adjusted by means of baking. PVDF films are characterized using Fourier transform infrared spectroscopy, X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The value of h0 can be estimated experimentally, and it is mainly affected by the wettability of the substrate, by the PVDF-DMF solution viscosity, by the initial angular acceleration of the plate providing a twisting force to the polymer. On the basis of previous studies [10,11] and using Equation (4), we can estimate that for the 20 wt.% PVDF film, h0 is in the range 8–20 μm, whereas for the 30 wt.% PVDF film it is in the range 40–70 μm. The density of the solution, ρ, is calculated using the following expression: ρ=Msolution/Vsolution, where Msolution=mPVDF+mDMF, being mPVDF and mDMF the measured masses of the PVDF and DMF respectively, and Vsolution=mPVDF/ρPVDF+mDMF/ρDMF, considering the density of PVDF …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The value of h0 can be estimated experimentally, and it is mainly affected by the wettability of the substrate, by the PVDF-DMF solution viscosity, by the initial angular acceleration of the plate providing a twisting force to the polymer. On the basis of previous studies [10,11] and using Equation (4), we can estimate that for the 20 wt.% PVDF film, h0 is in the range 8–20 μm, whereas for the 30 wt.% PVDF film it is in the range 40–70 μm. The density of the solution, ρ, is calculated using the following expression: ρ=Msolution/Vsolution, where Msolution=mPVDF+mDMF, being mPVDF and mDMF the measured masses of the PVDF and DMF respectively, and Vsolution=mPVDF/ρPVDF+mDMF/ρDMF, considering the density of PVDF …”
Section: Resultsmentioning
confidence: 90%
“…In References [2,11], the authors investigated the influence on the β-phase formation and the piezoelectric response enhancement of several process parameters. These included the polymer concentration (from 10 to 24 wt.%), the rotational speed ranging from 1000 rpm to 8000 rpm, and the crystallization temperature, in the range from 293 K to 363 K. It was shown that the β-phase increases in general with the rotation speed of the spin-coater, up to a limit value, which increases with the polymer concentration in the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simple process and good quality of prepared films, there has been a considerable amount of research on prompting the formation of β phase in spin-coated PVDF films [18,22,25,[35][36][37][38][39][40][41][42][43][44][45]. The general process can roughly be divided into three steps: solution preparation, spin-coating, and annealing.…”
Section: Spin-coating Methodsmentioning
confidence: 99%
“…The nucleation mechanism varies for specific fillers; therefore, important theories such as transcrystallization behavior [47,50] have been set up to describe the main interactions leading to nucleation. In most studies about spin-coating PVDF and its copolymers, the solution concentration is a factor that partially determines the thickness of the resulting film, and the rotational speed is another [25,40,41,43]. Spin-coating generally produces thicker films (>60 nm), but it is reported that films thinner than 10 nm can be achieved with improved experimental conditions [51][52][53].…”
Section: Spin-coating Methodsmentioning
confidence: 99%
“…Since the piezoelectric property in PVDF is related to the presence and amount of crystal structures in the material, the density changes in the peaks representing the β-crystal structure will inform us about the piezoelectricity of the material. The following formula will be used when making this evaluation [23,30,35]:…”
Section: Methodsmentioning
confidence: 99%